protection of non-traditional trademarks : critical perspectives - Calboli,Irene,Ed (OUP, 2018)
This volume offers a detailed analysis of the issues related to the protection of non-traditional marks. In recent years, the domain of trademark law and the scope of trademark protection has grown exponentially. Today, a wide variety of non-traditional marks, including colour, sound, smell, and shape marks, can be registered in many jurisdictions. However, this expansion of trademark protection has led to heated discussions and controversies about the impact of the protection of non-traditional marks on freedom of competition and, more generally, on socially valuable use of these or similar signs in unrelated non-commercial contexts. These tensions have also led to increasing litigation in this area across several jurisdictions. This book provides an overview of the debate and state of the law surrounding non-traditional marks at the international, regional, and national level. In particular, this book addresses relevant international treaties administered by the World Intellectual Property Organization (WIPO) and the Agreement on Trade-Related Aspects to Intellectual Property Rights (TRIPS) as well as several regional and national legislations and leading judicial decisions in order to examine current law and practice culminating in critical reflections and suggestions on the topic. --